Severe Cardiac Rupture by Only One Blow to the Chest in a Young Boy: An Autopsy Case. Issue 4 (21st November 2018) - Muramatsu, Hisanori; Umino, Keishi; Masuda, Hiroko; Ishizawa, Fujio; Sugano, Yukiko; Honda, Katsuya
Abstract: Cardiac rupture by blunt chest trauma is commonly seen after motor vehicle accidents and falls; however, it is rarely caused by a blow to the chest. We herein report an autopsy case of a high school boy who sustained severe right ventricular rupture by only one knee kick to the chest during a quarrel. He was hospitalized and developed cardiopulmonary arrest. Emergency surgery was performed, but the patient died. The autopsy revealed no external severe trauma or deformation, but the side wall of the right ventricle contained a large V‐shaped laceration. The other thoracic organs had no injuries. This case illustrates that severe cardiac rupture can occur by only one blow to the chest. Blunt cardiac injuries can occur even if no severe injuries are present on the body surface. We should consider the possibility of severe cardiac injuries regardless of the presence of external injuries.